Colonic Squamous Cell Carcinoma in Ulcerative Colitis: Report of a Case and Review of the Literature - Huilan Cheng; Michael D Sitrin; Sateesh K Satchidanand; Jan M Novak (Canadian Journal of Gastroenterology)
Squamous cell carcinoma (SCC) is a rare neoplasm in the colorectum. A case of SCC rising from an area of squamous metaplasia in the rectum is presented in a patient with long-standing ulcerative colitis and perianal warts. This is the first report in the literature describing the evolution of squamous metaplasia in the colonic mucosa into invasive carcinoma over time. Related literature on colorectal SCC and squamous metaplasia, and their relationships with inflammatory bowel disease and human papilloma virus, is reviewed.